2015
DOI: 10.1016/j.freeradbiomed.2015.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of Keap1 interactions with Nrf2

Abstract: Keap1 is a highly redox-sensitive member of the BTB-Kelch family that assembles with the Cul3 protein to form a Cullin–RING E3 ligase complex for the degradation of Nrf2. Oxidative stress disables Keap1, allowing Nrf2 protein levels to accumulate for the transactivation of critical stress response genes. Consequently, the Keap1–Nrf2 system is extensively pursued for the development of protein–protein interaction inhibitors that will stabilize Nrf2 for therapeutic effect in conditions of neurodegeneration, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
349
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(380 citation statements)
references
References 74 publications
1
349
0
3
Order By: Relevance
“…aldo-keto reductase, glutathione S-transferase, heme oxygenase-1, multidrug-resistance associated efflux pumps and NAD(P)H dehydrogenase quinone (NQO)-1 [6,7]. The level of Nrf2 protein is regulated by its inhibitor kelch-like ECH-associated protein (Keap1), and the binding of Keap1 to Nrf2 leads to its degradation in a ubiquitin-dependent manner [7,8]. Increased intracellular free radicals, such as reactive oxygen species (ROS), can trigger the dissociation of Keap1-Nrf2 complex, leading to nuclear translocation of Nrf2 and the transcriptional activation of its target genes through ARE in their promoter [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…aldo-keto reductase, glutathione S-transferase, heme oxygenase-1, multidrug-resistance associated efflux pumps and NAD(P)H dehydrogenase quinone (NQO)-1 [6,7]. The level of Nrf2 protein is regulated by its inhibitor kelch-like ECH-associated protein (Keap1), and the binding of Keap1 to Nrf2 leads to its degradation in a ubiquitin-dependent manner [7,8]. Increased intracellular free radicals, such as reactive oxygen species (ROS), can trigger the dissociation of Keap1-Nrf2 complex, leading to nuclear translocation of Nrf2 and the transcriptional activation of its target genes through ARE in their promoter [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress increases in models of PRC degeneration (36), and antioxidant treatment delays PRC death (4). Oxidative stress leads to increased levels of the transcription factor nuclear factor erythroid-derived 2-like 2 (NRF2), which translocates to the nucleus to up-regulate the expression of detoxifying and antioxidant genes (37,38). Compelling data from Cepko's laboratory (39) showed that subretinal delivery of Nrf2 using adeno-associated viral vectors in neonatal mice promoted the survival of PRC in retinal degeneration models.…”
mentioning
confidence: 99%
“…24,25 In response to oxidative stress, Nrf2 moves to the nucleus and binds to the antioxidant response element (ARE), which serves as a promoter sequence. 21,25 Furthermore, Nrf2 has been a new therapeutic target for demyelination in multiple sclerosis (MS).…”
Section: -23mentioning
confidence: 99%